The Colonial Endeavours of the Duchy of Courland, 1642–1698: A Forgotten Example of German Colonialism? - Freeman, John (German History, 2025)
The scope of German colonialism has fluctuated as perceptions about what it is to be a participant in colonialism have changed. Recent re-evaluations place German actors firmly within the early modern Atlantic world. Scholars have increasingly noted German investments in the slave trade, the exhibition of people of colour at German courts, and the presence of Germans in foreign colonies, to name some examples. One aspect of colonialism and the German-speaking world has nevertheless been overlooked for many decades. The Duchy of Courland and Semigallia, situated in modern-day Latvia, was a polity ruled by a Germanic nobility. In the mid-seventeenth century, Duke Jakob Kettler sought to better his precarious domestic situation through expanded trade and colonialism. Courland established outposts at the Gambia River in 1651 and the Caribbean island of Tobago in 1654. Although this presence was fleeting, Duke Jakob's ambitions remain a curious case study of how an eastern Baltic polity with little power approached global encounters. No substantial studies have been written on the subject since the 1970s, leaving the field mostly untouched by postcolonial, subaltern and entangled approaches. Many still-influential commentaries overemphasize national narratives, seeing the period as a Latvian golden age or a starting point for German imperialism. The article argues that this is an oversimplification of the varied identities, networks and influences present in Courland's colonial venture. It also asks how relevant the notion of German colonialism is to Courland and what can be learnt from recent German colonial scholarship.